Propriedades vibracionais e estruturais do ácido maleico em condições extremas de temperatura e pressão - Rufino, Francisco Marciano (2023)
Dicarboxylic acids have their properties investigated since the beginning of the last century, most of the time due to the unusual behavior of their chemical bonds, especially those of hydrogen, and the possibility of being co-crystallized with other materials and, with that, the appearance of intriguing characteristics. for science and technologically advantageous. They are present in vital processes of living beings and applied in various industrial sectors on a large scale. They are organic compounds that present in their structure two carboxyl functional groups whose molecular form can be written as (HOOC-R-COOH), where R is a radical that differentiates each acid of the family and can be an alkane, alkene or alkyne, linear chain or closed. Each acid can be found in more than one crystalline form. With the exception of oxalic acid, which has already been extensively studied, the other acids still have little data published in the literature, especially spectroscopic data under extreme conditions of pressure and temperature. The maleic acid crystals, object of study of this thesis, were obtained through aqueous solution by the method of slow evaporation of the solvent. The crystalline structure was confirmed by powder X-ray diffraction followed by Rietveld refinement and single crystal X-ray diffraction. Then, simultaneous thermoanalytical experiments (Thermogravimetry and Differential Scanning Calorimetry) were carried out at high temperatures, where a single event was verified in each technique close to 140 ◦C, and Differential Scanning Calorimetry at low temperatures in which no no changes. Then, Raman spectra were obtained under ambient conditions and vibrational theoretical calculations were performed. A Raman spectroscopy experiment was performed on maleic acid at high pressures (1 atm - 9 GPa) and two other Raman experiments were performed at high temperatures (30◦C-130◦C) and low (12K - 300K) temperatures covering the spectral region 100-3200 cm−1. In measurements as a function of temperature, only conformational changes were observed. At high pressure, spectra were obtained that suggest conformational changes around 2 GPa and 6 GPa. At these same pressure values, discontinuities were observed in the evolution of the unit cell volume in the X-ray powder diffraction experiment at high pressures (up to 10.1 GPa) carried out at Elettra Sincrontrone Trieste. Furthermore, an anisotropic decrease in lattice parameters and a 27% reduction in unit cell volume occurred.